Formation of high intensity ion beams with ballistic focusing; Journal of Physics: Conference Series; Vol. 927 : Applied Mathematics and Mechanics in the Aerospace Industry (AMMAI'2020) - Koval T. V. Tamara Vasilievna; Ryabchikov A. I. Aleksandr Ilyich; Shevelev A. E. Aleksey Eduardovich; Chan My Kim An; Tarakanov V. P. Vladimir Pavlovich (2017, 2017)
Title screen